Democracy and violence, in India and beyond. Issue 1 (7th June 2013) - Guha, Ramachandra
Abstract : HistorianRamachandra Guha analyses the causes and conditions of the violent struggles of Kashmiris in India and Tamils in Sri Lanka, and draws an alternative path between independence and assimilation that recognises and preserves the essential elements of democracy for all sides.